Development Of The Professional Potential At The Teacher As A Necessary Condition - Danikeeva, Aygul; Nurgaliyeva, Saniya; Rovnyakova, Irina; Stebletsova, Irina; Shaimerdenova, Zhadyra (Opción, 2019)
The aim of the study is to investigate the development of the professional potential at the teacher as a necessary condition for implementation of updating education via the methods of the analysis of normative documents, philosophical and psychological-pedagogical literature. As a result, ensuring continuity and integration of educational and professional activity is one of the main conditions of the development of professional and pedagogical potential. In conclusion, the professional potential of the teacher is defined by us as integrated professional and personal characteristics in which there is reflected the complex of the innovative knowledge